Enhancing emotional intelligence in medical education: a systematic review of interventions - Maity, Sabyasachi; De Filippis, Samantha Michelle; Aldanese, Alexander; McCulloch, Melissa A.; Sandor, Alexis P.; Perez Cajigas, Jan E.; Antoniadis, Yiorgos; Rochester, Te-keila D. T.; Carter, Lauren Elizabeth; Preisig, Alexander M.; Kobeissi, Julia Ali; Nayak, Narendra; et al. (Frontiers in Medicine, 2025)
IntroductionEmotional intelligence (EI) is a crucial competency for medical professionals, facilitating effective interpersonal relationships between physicians and patients. The ability to evaluate, regulate, and apply emotional understanding plays a significant role in fostering empathy, communication, and stress management. This systematic review aimed to determine the impact of various interventions on medical students’ EI development, academic performance, and overall patient care.MethodsA comprehensive literature search was conducted for studies published from 2021 until 2024, inclusion criteria focused on studies on medical students, employed validated EI assessment tools, and utilized appropriate research designs.Results44 articles met the inclusion criteria. The Joanna Briggs Institute (JBI) Critical Appraisal Checklist was applied to assess the quality of included studies. Although a meta-analysis was initially planned, substantial heterogeneity across the studies limited the pooling of quantitative data. Using an inductive coding approach, eight major themes were identified: Narrative and Storytelling Interventions, Reflective Practices and Writing, Communication Skills Training, Emotional Intelligence Enhancement, Experiential Learning and Patient Exposure, Stress, Burnout, and Coping Interventions, Assessment Tools and Structural Interventions, and Personalized Interventions and Diversity Considerations. These themes were subsequently mapped onto Daniel Goleman’s model of Emotional Intelligence to provide a structured theoretical framework.DiscussionThe findings of this review highlight that various interventions hold promise in enhancing EI among medical students, leading to improvements in personal well-being, communication skills, and professional development. The most effective approach appears to be a multifaceted, longitudinal integration of EI-focused strategies throughout medical training, incorporating repeated practice, guided reflection, faculty mentorship, and structured debriefing. The broader implications extend to improved doctor-patient relationships, reduced burnout, and enhanced clinical decision-making, ultimately contributing to higher patient satisfaction and more compassionate healthcare delivery. Future research should focus on refining intervention methodologies and assessing their long-term impact on medical education and practice.